The Contribution of Reading Activities Towards the Students Writing Performance - Yanpitherzon Liunokas (Ethical Lingua: Journal of Language Teaching and Literature, 2016)
Reading activities in this paper includes the habit of students in reading in their daily lives such as reading books, magazine, articles, online news and articles etc. Writing performance is the ability of students in expressing their ideas in written forms or paragraph. The aimed of the research is to find out the contribution of reading activities towards the students writing performance. This research applied descriptive method to describe the correlation between the reading activities and the students’ ability in writing. This research was conducted at SMAN 1 Soe, Kabupaten Timur Tengah Selatan (TTS), NTT. Findings of the research show that the reading habits of students have significant contribution towards the students’ writing ability. Mean score the reading is 81.13 and standard deviation is 8.26 and writing mean score is 68.93 and standard deviation is 8.12. The correlation test using Pearson Product Moment with SPSS 20 software program found that the score of significance is 991, which is higher than α score (991 ≥ 07), is classified as a good correlation. It indicates that when the students have a good reading habit, it will give good contribution towards their competence in writing.